Numerical investigation on improvement of energy transfer in solar power satellite. (April 2020) - Meng, Xianlong; Du, Kun; Bai, Xiaohui; Mankins, John C.; Liu, Cunliang
Abstract: Solar power satellite (SPS) normally collects sunlight through concentrating solar collectors give to PV cells which convert it to electric power and then transmitted it to the earth by microwave energy. SPS-ALPHA Mark-Ⅱ applies conical structural as the whole frame composed by several thousands of hexagonal "Reflectors and Deployment Modules" (RDM) that enables extremely high modularity and low cost of machining/space transport. SPS-ALPHA system, on the whole, can be treated a dense array concentrated photovoltaic (DA-CPV) system. The blocking shadow effect and cosine effect of ray path exist that make the optical efficiency fluctuate with different tracking angles, resulting the trade-off exists between optical efficiency and irradiance uniformity. The current study aims to find a compromise solution: a high optical efficiency with stable irradiance distribution for effective PV layout design. To meet this target, Ant Colony Optimization (ACO) algorithm combined with dynamic source-target mapping was adopted to find suitable aiming vectors of modular reflectors. The optical transmission characteristics were investigated using Monte-Carlo ray tracing (MCRT) method. Using above method, this article will focus on the effects of tracking conditions, structural and RDM parameters of SPS-ALPHA Mark-Ⅱ thereby provide basic data and reference for engineering constructions in next step. Highlights: This work firstly presents the optimization and optical sensitivity analysis of SPS-ALPHA Mark-Ⅱ. Cosine effect and blocking shadow effect make the optical efficiency unstable. Ant Colony Optimization (ACO) algorithm combined with dynamic source-target mapping was adopted. The optimized energy achieves apparent improvement and similar changing trend. The model can mostly ensure high output efficiency at every moment on orbit.